2022
DOI: 10.1038/s41598-022-18634-6
|View full text |Cite
|
Sign up to set email alerts
|

The first assimilation of Akatsuki single-layer winds and its validation with Venusian atmospheric waves excited by solar heating

Abstract: The planetary missions including the Venus Climate Orbiter ‘Akatsuki’ provide new information on various atmospheric phenomena. Nevertheless, it is difficult to elucidate their three-dimensional structures globally and continuously only from observations because satellite observations are considerably limited in time and space. We constructed the first ‘objective analysis’ of Venus’ atmosphere by assimilating cloud-top horizontal winds on the dayside from the equator to mid-latitudes, which is frequently obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Fujisawa et al. (2022) found that the energy density of the thermal tides at the equator had a maximum at 70–75 km and decreased above 75 km in analysis, while it was almost constant above 70 km in FRF. This can be also explained in terms of the difference of the vertical group velocities of the thermal tides between analysis and FRF.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fujisawa et al. (2022) found that the energy density of the thermal tides at the equator had a maximum at 70–75 km and decreased above 75 km in analysis, while it was almost constant above 70 km in FRF. This can be also explained in terms of the difference of the vertical group velocities of the thermal tides between analysis and FRF.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in Section 1, we use the first objective analysis data (hereinafter referred to as “analysis”) of Fujisawa et al. (2022), which was produced by assimilating the horizontal winds obtained from long‐term continuous measurements by UVI onboard Akatsuki conducted from September to December in 2018. Because the orbit of Akatsuki is equatorial, the UVI measurements can observe the dayside region in low‐ and mid‐latitudes, so that the horizontal winds can be derived at the cloud top level (∼70 km altitude) in latitudes equatorward of ∼50°.…”
Section: Model Settingmentioning
confidence: 99%
See 3 more Smart Citations